Battlestar Galactica. Season 1 [videorecording (DVD)] - Olmos, Edward James; McDonnell, Mary; Rymer, Michael, 1963-; Sackhoff, Katee; Bamber, Jamie, 1973-; Callis, James; Helfer, Tricia; Rymer, Michael, 1963- (Universal, 2005)
After losing the war against the Cylon robots, the Battlestar Galactica crew heads toward the fabled 13th colony, Earth. Galactica Commander Adama and President Laura Roslin are facing the problems of waning supplies and crushed morale. Along the way they have to deal with the credible threat that Cylons may be aboard the ship.